Sistem Informasi Inventori Obat Pada Apotek Berbasis Web (Studi Kasus: Apotek Asembagus Situbondo) - Alnaufal G, Muhammad Firmansyah; Widodo, Sugeng (LPPM STIKI MALANG, 2020)
Asembagus Pharmacy is an individual company engaged in medicine ranging from the procurement of medicines to the sale of medicines to the general public. In the company's operational process, Asembagus Pharmacy still uses conventional methods. Where in the process there are problems in managing drug data and drug reports. So to overcome this, a system that can help speed up the management of drug data and reports is needed. This system is designed using DFD, ERD, flowchart and using CI framework. The languages used are PHP, HTML, javascript and MySQL database. Tests conducted on the system using the black box method that looks at every function in the system. in accordance with the results of testing that has been done, that this system can help speed up the management of drug data and reports.